Pemanfaatan Artikel sebagai Strategi Meningkatkan Brand Awareness AMD Academy dan Sarana Mengedukasi Masyarakat - Chaterine Aritonang; Wahyu Fahrul Ridho (Universitas Katolik Widya Karya Malang, 2023)
This journal discusses the utilization of articles as an effective means to enhance company's brand awareness while educating the public. In the ever-evolving digital era, companies need to employ communication strategies that effectively reach their target audience. This approach entails using informative and industry-relevant articles. The research involves analyzing the needs and preferences of the public regarding desired information. Based on the analysis, a series of articles are produced to fulfill the public's information needs and simultaneously promote the company's brand. These articles are published across various online platforms, including the company's website, blog, and social media. The results demonstrate a significant increase in brand awareness and public recognition of the company through the implementation of this strategy. Additionally, the articles provide educational benefits to the public by presenting valuable and industry-relevant topics. The utilization of articles as a means to enhance brand awareness while educating the public offers diverse advantages. It enables companies to expand their reach, improve consumer trust, and strengthen their market position. Simultaneously, the public gains access to valuable and beneficial information, enhancing their knowledge and deriving direct benefits from the provided articles. Therefore, this strategy effectively fosters positive relationships between companies and consumers while contributing to the overall literacy and knowledge enhancement of the public.